The value of cerebrospinal fluid cytology in the diagnosis of atypical medulloblastoma: a case report and review of the literature - Xu, Shaoqiang; Cheng, Lina; Huang, Chunxia; Ye, Yuanyang; Lai, Keyuan (Frontiers in Medicine, 2025)
Medulloblastoma is a highly aggressive malignant tumor of the central nervous system in children, and early diagnosis is crucial for improving prognosis. In this article, we report a case of an 8-year-old male patient who presented with intermittent headache and vomiting, and whose cranial MRI showed subcerebellar tonsillar herniation with hydrocephalus, but lacked the typical features of tumor enhancement and was misdiagnosed as meningitis. After obtaining a cerebrospinal fluid specimen via lumbar puncture, tumor cells were found in it, which led to the diagnosis of medulloblastoma. This study provides a practical model for the differential diagnosis of atypical medulloblastoma on imaging and highlights the irreplaceable role of cerebrospinal fluid cytology in the identification of tumor metastasis.